English for Academic Writing - Latisha Asmaak Shafie; Mohammad Fadhili Yahya; Mahani Mansor; Nazira Osman (Oxford Fajar, 2017)
This comprehensive academic writing guide is tailored for students who are pursuing academic writing courses at institutions of higher learning. It covers the essential skills and genres in 12 units, which are designed as independent units to make this book more accessible to all learners. The fundamentals covered for effective academic writing include the use of appropriate tone, structure, vocabulary, register and stance in academic writing and how to paraphrase, summarise, analyse, synthesis and evaluate information from academic texts. Besides that, students are guided on the importance of citing their sources of information using the APA format and how to prepare complete references properly. They are also guided on how to respond critically to the texts, plan and write essays, prepare annotations, write reports and describe non-linear texts, which are all critical elements for academic writing success.